Chronic hypertension, perinatal mortality and the impact of preterm delivery: a population‐based study. (6th October 2021) - Grover, S; Brandt, JS; Reddy, UM; Ananth, CV
Abstract : Objectives: To estimate the association between chronic hypertension and perinatal mortality and to evaluate the extent to which risks are impacted by preterm delivery. Design: Cross‐sectional analysis. Setting: United States, 2015–18. Population: Singleton births (20–44 weeks of gestation). Exposure: Chronic hypertension, defined as elevated blood pressure diagnosed before pregnancy or recognised before 20 weeks of gestation. Main outcomes and measures: We derived the risk of perinatal mortality in relation to chronic hypertension from Poisson models, adjusted for confounders. The impacts of misclassification and unmeasured confounding were assessed. Causal mediation analysis was performed to quantify the impact of preterm delivery on the association. Results: Of the 15 090 678 singleton births, perinatal mortality rates were 22.5 and 8.2 per 1000 births in chronic hypertensive and normotensive pregnancies, respectively (adjusted risk ratio 2.05, 95% CI 2.00–2.10). Corrections for exposure misclassification and unmeasured confounding biases substantially increased the risk estimate. Although causal mediation analysis revealed that most of the association of chronic hypertension on perinatal mortality was mediated through preterm delivery, the perinatal mortality rates were highest at early term, term and late term gestations, suggesting that a planned early term delivery at 37–38 6/7 weeks may optimally balance risk in these pregnancies. Additionally, 87% (95% CI 84–90%) of perinatal deaths could be eliminated if preterm deliveries, as a result of chronic hypertension, were preventable. Conclusions: Chronic hypertension is associated with increased risk for perinatal mortality. Planned early term delivery and targeting modifiable risk factors for chronic hypertension may reduce perinatal mortality rates. Tweetable abstract: Maternal chronic hypertension is associated with increased risk for perinatal mortality, largely driven by preterm birth. Tweetable abstract: Maternal chronic hypertension is associated with increased risk for perinatal mortality, largely driven by preterm birth.